2021
DOI: 10.1177/10760296211019465
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Platelets and Endothelial-Derived Microparticles in Patients With Non-Valvular Atrial Fibrillation During Rivaroxaban Therapy

Abstract: It is known that atrial fibrillation (AF) is associated with the procoagulant state. Several studies have reported an increase of circulating microparticles in AF, which may be linked to a hypercoagulable state, atrial thrombosis and thromboembolism. We evaluated in our study alterations in both platelet (PMP, CD42b) and endothelial-derived (EMP, CD144) microparticle levels on anticoagulant therapy with rivaroxaban in nonvalvular AF. After administration of rivaroxaban, PMP levels were increased (median, [IQR]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Moreover, the size is critical in determining the hemocompatibility of microparticles when administered parenterally. The human body naturally produces microparticles under pathologic conditions (e.g., cancer, endothelial alterations, inflammation) [59][60][61], resulting from membrane blebbing as part of cell apoptosis [62]. Artificial microparticles (e.g., DPNs) can mitigate this risk by minimizing protein adsorption (e.g., through their materials) and by tuning the particle materials properties (i.e., particle deformability and size).…”
Section: Particles In Systemic Administrationmentioning
confidence: 99%
“…Moreover, the size is critical in determining the hemocompatibility of microparticles when administered parenterally. The human body naturally produces microparticles under pathologic conditions (e.g., cancer, endothelial alterations, inflammation) [59][60][61], resulting from membrane blebbing as part of cell apoptosis [62]. Artificial microparticles (e.g., DPNs) can mitigate this risk by minimizing protein adsorption (e.g., through their materials) and by tuning the particle materials properties (i.e., particle deformability and size).…”
Section: Particles In Systemic Administrationmentioning
confidence: 99%
“…EVs have been investigated as biomarkers in cancer because they are shed into the circulation from primary tumors (Melo et al, 2015;Zhang et al, 2017), because they can potentially be used for the early detection of metastasis (Guan et al, 2015;Saugstad et al, 2017), and because they can provide information about the disease through a easily obtained biological fluid like blood, urine, or saliva (Poulet et al, 2019). The cargo of EVs can also be used as biomarkers for neurodegenerative diseases (Hornung et al, 2020;Saugstad et al, 2017), as was demonstrated for Alzheimer's (Lee et al, 2019) and Parkinson's diseases (Russo et al, 2012), and for cardiovascular diseases (Huang et al, 2021;Lenart-Migdalska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also noticed that the levels of circulating MVs enriched in pro-coagulant lipids (phosphatidylserine) did not significantly differ between the AF patients and healthy volunteers. On the contrary, there is a large amount of evidence regarding the fact that circulating pro-coagulant MVs were found in abundance in patients with persistent and/or permanent AF who were not receiving anticoagulant therapy compared to age-matched control subjects [76][77][78]. It is interesting to note that a number of platelet-derived MVs and endothelial cell-derived MVs were not distinguished in patients with non-valvular AF and control subjects with CV risk factors, but the total amount of EVs was significantly higher in the AF patients than it was in in healthy volunteers without known CV risk factors [76][77][78].…”
Section: Atrial Fibrillation and Signature Of Evsmentioning
confidence: 99%
“…On the contrary, there is a large amount of evidence regarding the fact that circulating pro-coagulant MVs were found in abundance in patients with persistent and/or permanent AF who were not receiving anticoagulant therapy compared to age-matched control subjects [76][77][78]. It is interesting to note that a number of platelet-derived MVs and endothelial cell-derived MVs were not distinguished in patients with non-valvular AF and control subjects with CV risk factors, but the total amount of EVs was significantly higher in the AF patients than it was in in healthy volunteers without known CV risk factors [76][77][78]. However, the presence of AF was found to be a solid predictor of the annexin V(+) MVs level, which seems to be a marker for hypercoagulation and a risk of both atrial thrombosis and systemic thromboembolism.…”
Section: Atrial Fibrillation and Signature Of Evsmentioning
confidence: 99%